Festiqueijo : cultura, lazer e turismo - Baccon, Melissa (My University, 2014)
The party is characterized as a universal phenomenon, a product of collective action of human life that promotes particular culture. The party in question is the Festiqueijo, Gastronomic Festival of Cheese and a Cheese Festival, held annually in July in the municipality of Carlos Barbosa/RS/Brazil since 1987. So in 2008 was the eighteenth time it was held. It brings together several dairies and wineries of the Sierra Gaucha in a closed environment. The festival is usually visited by tourists from various parts of the state, country and even abroad. The aim of this study is to describe the history of Festiqueijo record with the emergence of the event and the changes that occurred over the years. The study also identifies the characteristics of Festiqueijo as a tourist attraction and the factors that promote the culture, business and tourism, considering it is an event that attracts visitors and tourists, and besides this, there was no record of the historical trajectory. The theoretical framework focuses on issues concerning the party, culture, leisure, event and food and cultural heritage. We used document analysis, interviews, observations and field notes and strategies for collecting information from the study. Document analysis allowed the rescue of the historical background of the festival and, as appropriate, other instruments complemented the collection of information. Through analysis and interpretation of information collected, we could see that the Festiqueijo emerged as a parallel event to a bigger party, the Party of milk, which happened in the city and that over the years, has not occurred, giving rise to the creation of Festiqueijo as the main event of the municipality. The study revealed that the Festiqueijo promotes culture, business and tourism, in addition to being in the cultural heritage of the city.
A festa caracteriza-se como um fenômeno universal, produto da ação coletiva da vida humana que promove determinada cultura. A festa em estudo é o Festiqueijo, Festival Gastronômico do Queijo ou Festa do Queijo, que ocorre anualmente no mês de julho no município de Carlos Barbosa/RS/Brasil desde 1987 e que em 2008 realizou a décima nona edição. Reúne diversas queijarias e vinícolas da Serra Gaúcha em um ambiente fechado. A festa costuma ser visitada por turistas oriundos de várias localidades do estado, do país e, inclusive, do exterior. O objetivo deste estudo consiste em descrever a trajetória histórica do Festiqueijo com registro do surgimento do evento e das modificações que ocorreram ao longo dos anos. O estudo identificou também as características do Festiqueijo como atrativo turístico e os elementos que promovem a cultura, as empresas e o turismo, considerando ser um evento que atrai visitantes e turistas e, ainda, que não havia registro da trajetória histórica. O referencial teórico está centrado nas questões referentes à festa, cultura, lazer, evento e gastronomia como patrimônio cultural. Utilizou-se análise documental, entrevistas, observações e notas de campo como estratégias de coleta de informações do estudo. A análise documental permitiu o resgate da trajetória histórica do festival e, a partir disso, os demais instrumentos complementaram a coleta de informações. Por meio da análise e da interpretação das informações coletadas, pôde-se constatar que o Festiqueijo surgiu como um evento paralelo de uma festa maior, a Festa do Leite, que acontecia no município e que, com o passar dos anos, deixou de acontecer, dando lugar à realização do Festiqueijo como evento principal do município. O estudo revelou que o Festiqueijo promove a cultura, as empresas e o turismo, além de se constituir em patrimônio cultural do município.
Keywords: TURISMO; Turismo; Cultura; Festa; Festival gastronômico; Festiqueijo; Gastronomia; Carlos Barbosa (RS); Tourism; Culture; Party; Gastronomic festival; Festiqueijo; Gastronomy